Challenges of English Language Teaching to Ethnic Students at the Secondary Level in Bangladesh (Global Journal of Human-Social Science, 2024)
This study investigates the challenges and problems connected with teaching English to secondary-level Garo students in Bangladesh. The study investigates the perspectives of English teachers and Garo students, identifying the challenges encountered both in the context and the techniques used to address these issues. The study used a mixed-method approach, combining quantitative and qualitative data collection tools such as surveys, teacher interviews, class observations, and focus group discussions (FGDs) to arrive at a full understanding of the topic. The findings highlight the importance of using culturally responsive teaching methods, reducing class sizes, incorporating Garo cultural elements into the curriculum, and improving teacher education. Furthermore, the study reveals socioeconomic challenges and the need for more real-world language practice opportunities outside of the classroom. This study emphasises the importance of implementing inclusive, culturally sensitive, and effective English as a Second Language (ESL) teaching approaches, particularly for ethnic minority groups like the Garo, in order to improve their educational experiences and outcomes.
Keywords: challenges; teaching english; garo students; perspectives; ethnicity; methods